2014
DOI: 10.1098/rsif.2014.0848
|View full text |Cite
|
Sign up to set email alerts
|

Escape trajectories are deflected when fish larvae intercept their own C-start wake

Abstract: Fish larvae may intercept their own wake during sharp turns, which might affect their escape performance. We analysed C-starts of larval zebrafish (Danio rerio, Hamilton, 1822) using a computational fluid dynamics approach that simulates free swimming (swimming trajectory is determined by fluid forces) by coupling hydrodynamics and body dynamics. The simulations show that fish may intercept their own wake when they turn by 100-1808. During stage 1 of a C-start, the fish generates a strong jet at the tail that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…We developed an in-house three-dimensional numerical approach programmed in FORTRAN 90 to simulate cyclic swimming of larval fish [7,16]. The model fish swims in the horizontal plane (3 degrees of freedom): centre-of-mass (CoM) movements and body orientation are determined by the hydrodynamic forces on the body, obtained by coupling the hydrodynamic and body-dynamic solutions (electronic supplementary material, § §B1 and 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed an in-house three-dimensional numerical approach programmed in FORTRAN 90 to simulate cyclic swimming of larval fish [7,16]. The model fish swims in the horizontal plane (3 degrees of freedom): centre-of-mass (CoM) movements and body orientation are determined by the hydrodynamic forces on the body, obtained by coupling the hydrodynamic and body-dynamic solutions (electronic supplementary material, § §B1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…These surfaces form an envelope around vortices but not dipoles [24], whose vorticity fields might be mistaken for vortices. The Q isosurfaces reveal turgid edge vortices along the fin fold (at Q ¼ 10) and in the wake (Q ¼ 0.1; [16]). The vortices identified by the Q-criterion agree with the vortices shown by the x-axis vorticity value.…”
Section: Edge Vortices Form Along the Undulating Fin Foldmentioning
confidence: 99%
“…To produce these forces, fish produce fluid-dynamic jets. During stage 1, fish larvae 358 produce a jet flow into the C-shape (Li et al, 2014;Müller et al, 2008). A CFD simulation of a 359 single zebrafish larva swimming sequence (Li et al, 2012) showed that initially this mainly 360 produces a torque that reorients the fish.…”
Section: Producing Acceleration 347mentioning
confidence: 99%
“…Johansen et al [12] estimated 26 that trailing fish in a school (striped surfperch Embiotoca lateralis) benefited from over 27 25% reduction in oxygen consumption, based on correlations between swimming speeds, 28 pectoral fin beat frequency, and oxygen consumption of solitary fish. Marras et al [13] 29 also inferred reduced costs of swimming from measurements of tail-beat frequency of 30 grey mullet Liza aurata alone and in schools, combined with relationships between 31 tail-beat frequency and activity metabolism. Interestingly, they found that all members 32 of the school received energetic benefit regardless of their spatial position relative to 33 neighbors.…”
mentioning
confidence: 98%
“…A physical description of the local interactions between nearest neighbors, 70 which are crucial in determining the whole group dynamics, still needs deeper insight. 71 We therefore study the minimal subsystem of fish school, consisting in two fish 72 swimming together, using a three-dimensional computational approach developed by Li 73 et al [29][30][31]. We investigate the consequences of spatial organization and kinematic 74 synchronization on the energy expenditure of the two-fish school (see Fig.…”
mentioning
confidence: 99%